Special anti-corrosion and wear-resistant coating for heat exchanger and preparation method thereof

By using film-forming substances such as epoxy resin and polyurethane resin, combined with zinc powder, zinc phosphate and other materials, an anticorrosion coating with high adhesion, chemical resistance and wear resistance is prepared, which solves the problem of poor adhesion of traditional coatings and meets the long-term use needs of heat exchangers under complex working conditions.

CN119662106AInactive Publication Date: 2025-03-21SHANDONG WEIDE REMANUFACTURING TECH CO LTD

Patent Information

Application Number
CN202411961426.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional anti-corrosion and wear-resistant coatings have poor adhesion on the surface of the heat exchanger, which is difficult to meet the long-term use needs of the heat exchanger under complex operating conditions.

Method used

Epoxy resin and polyurethane resin are used as film forming substances, combined with zinc powder, zinc phosphate, silicon carbide and alumina and other materials, and through dispersion, grinding and curing processes, an anticorrosion coating with high adhesion, chemical resistance and wear resistance is prepared.

Benefits of technology

It significantly improves the adhesion and chemical resistance of the coating, enhances the corrosion and wear resistance of the heat exchanger surface, and meets the long-term use needs under complex working conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a special anti-corrosion and wear-resistant coating for a heat exchanger and a preparation method thereof, and relates to the technical field of coating processing, and the special anti-corrosion and wear-resistant coating comprises the following components in parts by mass: 10-20 parts of epoxy resin, 25-35 parts of polyurethane resin, 10-25 parts of zinc powder, 18-38 parts of zinc phosphate, 8-18 parts of silicon carbide, 15-37 parts of aluminum oxide and 10-22 parts of an auxiliary agent. The coating is prepared through the following preparation steps that firstly, the raw materials are pretreated; 2, mixing and dispersing the pretreated raw materials; 3, grinding and refining the anti-corrosion pigment and the wear-resistant filler in the film forming substance; and 4, adjusting the viscosity, namely adding a proper amount of curing agent into the ground coating, slowly and uniformly stirring, and finally adjusting the viscosity of the coating by using a diluent according to the construction requirements of the coating. The epoxy resin and the polyurethane resin are used as film forming substances, so that a firm coating can be well formed, good adhesive force and chemical resistance are further provided, and the adhesive force of the coating is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating processing, in particular to a special anti-corrosion and wear-resistant coating for a heat exchanger and a preparation method thereof. Background Art

[0002] Heat exchangers are widely used in various heat exchange processes in industrial production. Their working environment is complex and they face problems such as corrosion and wear. These problems not only affect the normal operation of the heat exchanger, but may also cause equipment damage, energy waste and safety hazards. Therefore, the development of an efficient, durable, anti-corrosion and wear-resistant coating is of great significance to ensure the long-term and stable operation of the heat exchanger.

[0003] Traditional anti-corrosion and wear-resistant coatings can protect the surface of heat exchangers to a certain extent, but they often have the problem of poor adhesion. With the development of industrial production, the performance requirements of heat exchangers are constantly increasing, causing the coating on the surface of heat exchangers to fall off frequently, resulting in the existing anti-corrosion coatings being unable to meet the long-term use requirements of heat exchangers under complex working conditions. Summary of the invention

[0004] Technical problem to be solved: In view of the shortcomings of the prior art, the present invention provides a special anti-corrosion and wear-resistant coating for a heat exchanger and a preparation method thereof, which solves the problem that traditional anti-corrosion and wear-resistant coatings can protect the surface of the heat exchanger to a certain extent, but often have poor adhesion. With the development of industrial production, the performance requirements of heat exchangers are constantly improving, resulting in frequent shedding of the coating on the surface of the heat exchanger, making it difficult for existing anti-corrosion coatings to meet the long-term use requirements of the heat exchanger under complex working conditions.

[0005] Technical solution: To achieve the above purpose, the present invention is implemented by the following technical solution: a special anti-corrosion and wear-resistant coating for heat exchangers, comprising the following formula in parts by mass: 10-20 parts of epoxy resin, 25-35 parts of polyurethane resin, 10-25 parts of zinc powder, 18-38 parts of zinc phosphate, 8-18 parts of silicon carbide, 15-37 parts of aluminum oxide and 10-22 parts of additives; The auxiliary agent includes a dispersant, a defoamer and a curing agent in parts by mass.

[0006] A method for preparing a special anti-corrosion and wear-resistant coating for a heat exchanger comprises the following preparation steps: Step 1: Pre-treat the raw materials, sieve the anti-corrosion pigments such as zinc powder and zinc phosphate and the wear-resistant fillers such as silicon carbide and aluminum oxide respectively to remove large particle impurities, and heat the film-forming materials such as epoxy resin and polyurethane resin to an appropriate temperature to reduce their viscosity for subsequent mixing operations; Step 2: Mix and disperse the pretreated raw materials, put the pretreated film-forming material into a high-speed disperser, add a dispersant under low-speed stirring, then slowly add anticorrosive pigments and wear-resistant fillers, and increase the stirring speed to fully disperse the anticorrosive pigments and wear-resistant fillers in the film-forming material, and then add a defoaming agent to eliminate bubbles generated during the stirring process; Step 3: Grind and refine the anticorrosive pigment and wear-resistant filler in the film-forming material. Put the mixed and dispersed coating into a sand mill for grinding. The particles of the anticorrosive pigment and wear-resistant filler can be further refined by grinding. Step 4: Adjust the viscosity. Add an appropriate amount of curing agent to the ground paint and stir slowly and evenly. Finally, use a thinner to adjust the viscosity of the paint according to the construction requirements of the paint.

[0007] Furthermore, in the step 1, screening is performed using a 200-300 mesh screen. In order to prevent the anti-corrosion pigment and the wear-resistant filler from being oxidized and thus affecting their performance, the anti-corrosion pigment and the wear-resistant filler need to be processed in an inert gas environment.

[0008] Furthermore, in the step 1, the epoxy resin needs to be heated to 40-60° C., and the polyurethane resin needs to be heated to 50-70° C. At the same time, attention should be paid to stirring during the heating process to prevent local overheating.

[0009] Furthermore, in the step 2, the low-speed stirring rate is 300-500 r / min, and the stirring time is 5-10 min, the high-speed stirring rate is 1000-1500 r / min, and the stirring time is 30-60 min, and high-speed stirring is required for 10-15 min after adding the defoaming agent.

[0010] Furthermore, the grinding medium in step three is glass beads or zirconium oxide, and the particle size of the medium is 0.8-1.2 mm, and the grinding time is 2-4 hours. The fineness of the coating after grinding is 30-50 μm, thereby improving the density and glossiness of the coating.

[0011] Furthermore, the amount of curing agent added in step 4 is calculated based on the epoxy equivalent of the film-forming substance. For example, the amount of amine curing agent is usually 0.8-1.2 times the epoxy equivalent of epoxy resin. The viscosity of the coating needs to be controlled at 60-80s during construction, and the coating after adjusting the viscosity can be used for anti-corrosion and wear-resistant coating of the heat exchanger after filtering through a 100-150 mesh filter.

[0012] Furthermore, the preparation process of the dispersant comprises the following steps: S1: After selecting the monomer, the initiator is prepared, and then the solvent is prepared; S2: First, a reaction device is built, then the monomer is prepolymerized, and finally the monomer is continuously added to make the polymer chain grow continuously to form an anionic polymer with a certain molecular weight; S3: firstly prepare an alkali solution, then add the alkali solution to the anionic polymer for neutralization, convert the acidic functional groups (such as carboxyl groups) in the polymer into salt form, so that the dispersant has better water solubility and dispersibility; S4: The neutralized dispersant solution contains a small amount of unreacted monomers, polymer gel and other impurities, which need to be removed by filtering. The filtered solution is then dried and concentrated to obtain a solid dispersant.

[0013] Furthermore, the preparation process of the defoamer comprises the following steps: S①: Select dimethyl silicone oil as the main component of the defoamer, and select dimethyl silicone oil with a viscosity between 100-1000mPa・s according to the specific application scenario. At the same time, prepare an emulsifier for dispersing silicone oil in the water phase, as well as other additives that can improve the performance of the defoamer; S②: Put the silicone oil and emulsifier solution into a reactor equipped with a stirrer and a thermometer, first stir at a low speed of 300-500r / min to make the silicone oil and emulsifier preliminarily mixed, then increase the stirring speed to 1000-2000r / min, and use a homogenizer or ultrasonic emulsifier to assist emulsification; S③: Filter the emulsified defoamer to remove incompletely emulsified silicone oil particles or other impurities, and then adjust the viscosity of the defoamer emulsion according to the amount of thickener added.

[0014] Furthermore, the preparation process of the curing agent comprises the following steps: Step 1: Select diethylenetriamine as the main component of the curing agent, and select other additives as auxiliary agents in order to adjust the performance of the curing agent; Step 2: placing diethylenetriamine and propylene oxide in a reaction kettle equipped with a stirrer, a thermometer and a reflux condenser for chemical reaction; Step 3: Filter the solid after the chemical reaction to remove incompletely reacted raw materials or reaction by-products.

[0015] Beneficial effects: The present invention provides a special anti-corrosion and wear-resistant coating for heat exchangers and a preparation method thereof. It has the following beneficial effects: In this solution, by using epoxy resin and polyurethane resin as film-forming substances, a strong coating can be well formed, thereby providing good adhesion and chemical resistance, which is beneficial to improving the adhesion of the coating.

[0016] In this scheme, zinc powder and zinc phosphate are used as anti-corrosion pigments, and the anti-corrosion effect is enhanced by sacrificial anode protection and other means, while silicon carbide and aluminum oxide give the coating good wear resistance.

[0017] In this solution, the use of a dispersant during the preparation process can effectively improve the uniformity of the distribution of anticorrosive pigments and wear-resistant fillers in the film-forming material, thereby improving the stability and construction performance of the coating. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Embodiment 1: The embodiment of the present invention provides a special anti-corrosion and wear-resistant coating for heat exchangers, which includes the following formula in parts by mass: 10 parts of epoxy resin, 25 parts of polyurethane resin, 10 parts of zinc powder, 18 parts of zinc phosphate, 8 parts of silicon carbide, 15 parts of aluminum oxide and 10 parts of additives; The additives include dispersants, defoamers and curing agents in parts by mass.

[0020] A method for preparing a special anti-corrosion and wear-resistant coating for a heat exchanger comprises the following preparation steps: Step 1: Pre-treat the raw materials, sieve the anti-corrosion pigments such as zinc powder and zinc phosphate and the wear-resistant fillers such as silicon carbide and aluminum oxide respectively to remove large particle impurities, and heat the film-forming materials such as epoxy resin and polyurethane resin to an appropriate temperature to reduce their viscosity for subsequent mixing operations; Screening is performed using a 300-mesh screen. In order to prevent the anti-corrosion pigment and wear-resistant filler from oxidation and thus affecting their performance, the anti-corrosion pigment and wear-resistant filler need to be processed in an inert gas environment. In step 1, the epoxy resin needs to be heated to 40°C, and the polyurethane resin needs to be heated to 50°C. At the same time, attention should be paid to stirring during the heating process to prevent local overheating; Step 2: Mix and disperse the pretreated raw materials, put the pretreated film-forming material into a high-speed disperser, add a dispersant under low-speed stirring, then slowly add anticorrosive pigments and wear-resistant fillers, and increase the stirring speed to fully disperse the anticorrosive pigments and wear-resistant fillers in the film-forming material, and then add a defoaming agent to eliminate bubbles generated during the stirring process; The low-speed stirring rate is 300r / min, and the stirring time is 5min. The high-speed stirring rate is 1000r / min, and the stirring time is 30min. At the same time, pay attention to the state of the coating during this process to avoid sedimentation or agglomeration of the filler. After adding the defoamer, high-speed stirring is required for 10min. Step 3: Grind and refine the anticorrosive pigment and wear-resistant filler in the film-forming material, put the mixed and dispersed coating into a sand mill for grinding, and the particles of the anticorrosive pigment and wear-resistant filler can be further refined by grinding. The grinding medium is glass beads or zirconium oxide, and the particle size of the medium is 0.8 mm, and the grinding time is 2 hours. The fineness of the coating after grinding is 30 μm, thereby improving the density and glossiness of the coating; Step 4: Adjust the viscosity. Add an appropriate amount of curing agent to the ground paint and stir slowly and evenly. Finally, adjust the viscosity of the paint with a thinner according to the construction requirements of the paint. The amount of curing agent added is calculated based on the epoxy equivalent of the film-forming substance. For example, the amount of amine curing agent is usually 0.8 times the epoxy equivalent of epoxy resin. The viscosity of the paint needs to be controlled at 60s during construction, and the paint after adjusting the viscosity can be used for anti-corrosion and wear-resistant coating of the heat exchanger after filtering through a 150-mesh filter.

[0021] The preparation process of the dispersant includes the following steps: S1: After selecting the monomer, the initiator is prepared, and then the solvent is prepared; Commonly used monomers include acrylic acid, methacrylic acid and maleic anhydride. These monomers contain acidic functional groups such as carboxyl groups, which can provide anionic properties. Taking acrylic acid as an example, high-purity acrylic acid monomers need to be selected, and the purity is generally required to be above 99% to ensure the accuracy of the reaction and product quality. Ammonium persulfate (APS) or sodium persulfate is a commonly used initiator. The amount of the initiator is generally 0.5% of the total weight of the monomer. For example, during the preparation process, the initiator needs to be prepared into an aqueous solution with a certain concentration, usually around 10%, so as to accurately control the amount of the initiator added during the reaction. The most commonly used solvent is water. For some special reactions, a small amount of organic solvents such as ethanol may be used to assist in dissolution. When using water as a solvent, the purity of the water must be ensured. Deionized water is generally used to prevent impurities in the water from interfering with the reaction. S2: First, a reaction device is built, then the monomer is prepolymerized, and finally the monomer is continuously added to make the polymer chain grow continuously to form an anionic polymer with a certain molecular weight; Place a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a dropping funnel in a constant temperature water bath. The reaction device must be well sealed to prevent solvent volatilization and impurities from entering during the reaction. Add part of the monomer (such as acrylic acid) and the initiator solution into a four-necked flask, start stirring and heat to the reaction temperature, which is generally between 70°C. At this stage, the monomer begins to polymerize to form oligomers. This process generally lasts for 30 minutes, in order to provide active centers for subsequent polymerization reactions. The remaining monomer and initiator solution are slowly added to the reaction system through a dropping funnel. The dropping time is generally controlled within 2 hours. During the dropping process, the reaction temperature should be kept stable. The monomers are uniformly involved in the polymerization reaction by stirring. With the continuous addition of monomers, the polymer chain continues to grow to form an anionic polymer with a certain molecular weight. S3: firstly prepare an alkali solution, then add the alkali solution to the anionic polymer for neutralization, convert the acidic functional groups (such as carboxyl groups) in the polymer into salt form, so that the dispersant has better water solubility and dispersibility; Select a suitable alkali for neutralization reaction. Commonly used alkalis are sodium hydroxide (NaOH) or potassium hydroxide (KOH). Prepare the alkali into an aqueous solution of a certain concentration, and control the concentration of the aqueous solution between 10% and 30%; After the polymerization reaction is completed, the temperature of the reaction system is lowered to 40-60°C, and then alkali solution is slowly added for neutralization. During the neutralization process, the addition rate of the alkali solution should be controlled to avoid excessive reaction. Through the neutralization reaction, the acidic functional groups (such as carboxyl groups) in the polymer are converted into salt forms, so that the dispersant has better water solubility and dispersibility. The degree of neutralization is controlled between 70%-100% and adjusted according to actual needs; S4: The neutralized dispersant solution contains a small amount of unreacted monomers, polymer gel and other impurities, which need to be removed by filtering, and then the filtered solution is dried and concentrated to obtain a solid dispersant; The dispersant solution needs to be filtered using filter paper or a filter screen. The mesh size of the filter screen is generally 500 meshes. When a solid dispersant is required, the filtered solution can be concentrated and dried. Concentration can be performed by vacuum distillation to evaporate the solvent at a lower temperature. Drying can be performed using a vacuum drying oven or a spray dryer to make the concentrated dispersant into a solid powder.

[0022] The preparation process of the defoamer includes the following steps: S①: Select dimethyl silicone oil as the main component of the defoamer, and select dimethyl silicone oil with a viscosity between 100-1000mPa・s according to the specific application scenario. At the same time, prepare an emulsifier for dispersing silicone oil in the water phase, as well as other additives that can improve the performance of the defoamer; The viscosity of dimethyl silicone oil is a key parameter that affects the defoaming performance and stability of the defoamer. Generally, silicone oils of different viscosities are selected according to specific application scenarios. At the same time, the purity of the silicone oil must be high and the impurity content must be low to ensure the quality of the defoamer. Commonly used emulsifiers include polyoxyethylene polyoxypropylene ether block copolymers (such as Pluronic series), sorbitan fatty acid esters (such as Span series), etc. The dosage of emulsifier is generally 10%-30% of the mass of silicone oil. The emulsifier needs to be prepared into an aqueous solution of a certain concentration, usually around 30%-50%, to facilitate accurate control of the dosage during the emulsification process; In order to improve the performance of the defoamer, some other additives can be prepared. For example, in order to enhance the stability of the defoamer, a small amount of thickener, such as sodium carboxymethyl cellulose (CMC), can be added; in order to improve the anti-foaming performance of the defoamer, a small amount of silicon dioxide powder can be added, and the particle size is 5-50μm; S②: Put the silicone oil and emulsifier solution into a reactor equipped with a stirrer and a thermometer, first stir at a low speed of 300r / min to make the silicone oil and emulsifier preliminarily mixed, then increase the stirring speed to 1000r / min, and use a homogenizer or ultrasonic emulsifier to assist emulsification; The initial mixing time is 10 minutes, the purpose of which is to create good conditions for the subsequent emulsification process. The emulsification time is 30 minutes, and during the emulsification process, the silicone oil is wrapped by the emulsifier and dispersed into tiny droplets to form an emulsion. By controlling the emulsification conditions, the particle size and stability of the emulsion can be adjusted. For example, by adjusting the stirring speed and emulsification time, the particle size of the emulsion can be controlled at 0.5μm, and the smaller the particle size, the more stable the emulsion and the better the defoaming performance; S③: Filter the emulsified defoamer to remove incompletely emulsified silicone oil particles or other impurities, and then adjust the viscosity of the defoamer emulsion according to the amount of thickener added; The emulsified defoamer emulsion may contain some incompletely emulsified silicone oil particles or other impurities, which need to be removed by filtering. You can use a 300-mesh filter to filter. After filtration, if you need to adjust the performance of the defoamer, such as adjusting the viscosity of the emulsion, you can add an appropriate amount of thickener or diluent. The amount of thickener added is generally adjusted according to the required viscosity. For example, adding 0.1% CMC can appropriately increase the viscosity of the emulsion; if dilution is required, add an appropriate amount of deionized water to make the defoamer reach the required concentration and performance.

[0023] For some application scenarios with high requirements for stability, the prepared defoamer can be tested for stability. The defoamer can be observed under different temperatures (such as 4°C, 25°C, 40°C) and storage times (such as 1 day, 7 days, 30 days) to check whether the emulsion is stratified or demulsified. If stability problems occur, they can be solved by adjusting the type and amount of emulsifier, adding stabilizer, etc.

[0024] The preparation process of the curing agent includes the following steps: Step 1: Select diethylenetriamine as the main component of the curing agent, and select other additives as auxiliary agents to adjust the performance of the curing agent. The purity of amine compounds is required to be high, generally above 99% to ensure the quality of the curing agent, because impurities may affect the speed and degree of the curing reaction. For example, if ethylenediamine contains impurities such as moisture, bubbles may be generated during the curing process, affecting the performance of the cured product; For example, in order to extend the application period of the curing agent, a small amount of retarder, such as salicylic acid, can be added. The amount of retarder is generally adjusted according to the specific curing requirements, usually 0.1% of the mass of the amine raw material; Step 2: placing diethylenetriamine and propylene oxide in a reaction kettle equipped with a stirrer, a thermometer and a reflux condenser for chemical reaction; Usually it involves reactions with other compounds, such as the reaction of fatty amines with compounds such as propylene oxide, which is carried out in a reactor equipped with a stirrer, a thermometer and a reflux condenser. First, the fatty amine is added to the reactor and heated to 60°C, and then propylene oxide is slowly added dropwise. During the reaction, the dropping speed and reaction temperature must be strictly controlled. The dropping speed is 1mL / min to prevent the reaction from being too violent. The reaction time is 2h. This reaction can modify the fatty amine and change its activity and curing properties. Step 3: Filter the solid after the chemical reaction to remove the unreacted raw materials or reaction by-products; If further refining is required, vacuum distillation and other methods can be used to remove low-boiling impurities and unreacted small molecules. The temperature and pressure of vacuum distillation should be adjusted according to the boiling point and other properties of the curing agent. For example, for some low molecular weight fatty amine curing agents, the vacuum distillation temperature can be controlled at 50°C and the pressure is 1 kPa.

[0025] Example 2: A special anti-corrosion and wear-resistant coating for heat exchangers, comprising the following formula in parts by mass: 20 parts of epoxy resin, 35 parts of polyurethane resin, 25 parts of zinc powder, 38 parts of zinc phosphate, 18 parts of silicon carbide, 37 parts of aluminum oxide and 22 parts of additives; The additives include dispersants, defoamers and curing agents in parts by mass.

[0026] A method for preparing a special anti-corrosion and wear-resistant coating for a heat exchanger comprises the following preparation steps: Step 1: Pre-treat the raw materials, sieve the anti-corrosion pigments such as zinc powder and zinc phosphate and the wear-resistant fillers such as silicon carbide and aluminum oxide respectively to remove large particle impurities, and heat the film-forming materials such as epoxy resin and polyurethane resin to an appropriate temperature to reduce their viscosity for subsequent mixing operations; Screening is performed using a 200-mesh screen. In order to prevent the anticorrosive pigment and wear-resistant filler from being oxidized and thus affecting their performance, the anticorrosive pigment and wear-resistant filler need to be processed in an inert gas environment. In step 1, the epoxy resin needs to be heated to 60°C, and the polyurethane resin needs to be heated to 70°C. At the same time, attention should be paid to stirring during the heating process to prevent local overheating; Step 2: Mix and disperse the pretreated raw materials, put the pretreated film-forming material into a high-speed disperser, add a dispersant under low-speed stirring, then slowly add anticorrosive pigments and wear-resistant fillers, and increase the stirring speed to fully disperse the anticorrosive pigments and wear-resistant fillers in the film-forming material, and then add a defoaming agent to eliminate bubbles generated during the stirring process; The low-speed stirring rate is 500r / min, and the stirring time is 10min. The high-speed stirring rate is 1500r / min, and the stirring time is 60min. At the same time, pay attention to the state of the coating during this process to avoid sedimentation or agglomeration of the filler. After adding the defoamer, high-speed stirring is required for 15min. Step 3: Grind and refine the anticorrosive pigment and wear-resistant filler in the film-forming material, put the mixed and dispersed coating into a sand mill for grinding, and the particles of the anticorrosive pigment and wear-resistant filler can be further refined by grinding. The grinding medium is glass beads or zirconium oxide, and the particle size of the medium is 1.2 mm, and the grinding time is 4 hours. The fineness of the coating after grinding is 50 μm, thereby improving the density and glossiness of the coating; Step 4: Adjust the viscosity. Add an appropriate amount of curing agent to the ground paint and stir slowly and evenly. Finally, adjust the viscosity of the paint with a thinner according to the construction requirements of the paint. The amount of curing agent added is calculated based on the epoxy equivalent of the film-forming substance. For example, the amount of amine curing agent is usually 1.2 times the epoxy equivalent of epoxy resin. The viscosity of the paint needs to be controlled at 80s during construction, and the paint after adjusting the viscosity can be used for anti-corrosion and wear-resistant coating of the heat exchanger after filtering through a 100-mesh filter.

[0027] The preparation process of the dispersant includes the following steps: S1: After selecting the monomer, the initiator is prepared, and then the solvent is prepared; Commonly used monomers include acrylic acid, methacrylic acid and maleic anhydride. These monomers contain acidic functional groups such as carboxyl groups, which can provide anionic properties. Taking acrylic acid as an example, high-purity acrylic acid monomers need to be selected, and the purity is generally required to be above 99% to ensure the accuracy of the reaction and product quality. Ammonium persulfate (APS) or sodium persulfate is a commonly used initiator. The amount of the initiator is generally 5% of the total weight of the monomer. For example, during the preparation process, the initiator needs to be prepared into an aqueous solution with a certain concentration, usually around 10%-30%, so as to accurately control the amount of the initiator added during the reaction; The most commonly used solvent is water. For some special reactions, a small amount of organic solvents such as ethanol may be used to assist in dissolution. When using water as a solvent, the purity of the water must be ensured. Deionized water is generally used to prevent impurities in the water from interfering with the reaction. S2: First, a reaction device is built, then the monomer is prepolymerized, and finally the monomer is continuously added to make the polymer chain grow continuously to form an anionic polymer with a certain molecular weight; Place a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a dropping funnel in a constant temperature water bath. The reaction device must be well sealed to prevent solvent volatilization and impurities from entering during the reaction. Add part of the monomer (such as acrylic acid) and the initiator solution into a four-necked flask, start stirring and heat to the reaction temperature, which is generally between 90°C. At this stage, the monomer begins to polymerize to form oligomers. This process generally lasts for 60 minutes, in order to provide active centers for subsequent polymerization reactions. The remaining monomer and initiator solution are slowly added to the reaction system through a dropping funnel. The dropping time is generally controlled within 4 hours. During the dropping process, the reaction temperature should be kept stable. The monomers are uniformly involved in the polymerization reaction by stirring. With the continuous addition of monomers, the polymer chain continues to grow to form an anionic polymer with a certain molecular weight. S3: firstly prepare an alkali solution, then add the alkali solution to the anionic polymer for neutralization, convert the acidic functional groups (such as carboxyl groups) in the polymer into salt form, so that the dispersant has better water solubility and dispersibility; Select a suitable alkali for neutralization reaction. Commonly used alkalis are sodium hydroxide (NaOH) or potassium hydroxide (KOH). Prepare the alkali into an aqueous solution of a certain concentration, and control the concentration of the aqueous solution between 10% and 30%; After the polymerization reaction is completed, the temperature of the reaction system is lowered to 60°C, and then alkali solution is slowly added for neutralization. During the neutralization process, the addition rate of the alkali solution should be controlled to avoid excessive reaction. Through the neutralization reaction, the acidic functional groups (such as carboxyl groups) in the polymer are converted into salt forms, so that the dispersant has better water solubility and dispersibility. The degree of neutralization is controlled between 100% and adjusted according to actual needs; S4: The neutralized dispersant solution contains a small amount of unreacted monomers, polymer gel and other impurities, which need to be removed by filtering, and then the filtered solution is dried and concentrated to obtain a solid dispersant; The dispersant solution needs to be filtered using filter paper or a filter screen. The mesh size of the filter screen is generally 100 meshes. When a solid dispersant is required, the filtered solution can be concentrated and dried. Concentration can be performed by vacuum distillation to evaporate the solvent at a lower temperature. Drying can be performed using a vacuum drying oven or a spray dryer to make the concentrated dispersant into a solid powder.

[0028] The preparation process of the defoamer includes the following steps: S①: Select dimethyl silicone oil as the main component of the defoamer, and select dimethyl silicone oil with a viscosity between 1000mPa・s according to the specific application scenario. At the same time, prepare an emulsifier for dispersing silicone oil in the water phase, as well as other additives that can improve the performance of the defoamer; The viscosity of dimethyl silicone oil is a key parameter that affects the defoaming performance and stability of the defoamer. Generally, silicone oils of different viscosities are selected according to specific application scenarios. At the same time, the purity of the silicone oil must be high and the impurity content must be low to ensure the quality of the defoamer. Commonly used emulsifiers include polyoxyethylene polyoxypropylene ether block copolymers (such as Pluronic series), sorbitan fatty acid esters (such as Span series), etc. The dosage of emulsifier is generally 10%-30% of the mass of silicone oil. The emulsifier needs to be prepared into an aqueous solution of a certain concentration, usually around 30%-50%, to facilitate accurate control of the dosage during the emulsification process; In order to improve the performance of the defoamer, some other additives can be prepared. For example, in order to enhance the stability of the defoamer, a small amount of thickener, such as sodium carboxymethyl cellulose (CMC), can be added; in order to improve the anti-foaming performance of the defoamer, a small amount of silicon dioxide powder can be added, and the particle size is 5-50μm; S②: Put the silicone oil and emulsifier solution into a reactor equipped with a stirrer and a thermometer, first stir at a low speed of 500r / min to make the silicone oil and emulsifier preliminarily mixed, then increase the stirring speed to 2000r / min, and use a homogenizer or ultrasonic emulsifier to assist emulsification; The initial mixing time is 20 minutes, the purpose of which is to create good conditions for the subsequent emulsification process. The emulsification time is 60 minutes, and during the emulsification process, the silicone oil is wrapped by the emulsifier and dispersed into tiny droplets to form an emulsion. By controlling the emulsification conditions, the particle size and stability of the emulsion can be adjusted. For example, by adjusting the stirring speed and emulsification time, the particle size of the emulsion can be controlled at 5μm, and the smaller the particle size, the more stable the emulsion and the better the defoaming performance; S③: Filter the emulsified defoamer to remove incompletely emulsified silicone oil particles or other impurities, and then adjust the viscosity of the defoamer emulsion according to the amount of thickener added; The emulsified defoamer emulsion may contain some incompletely emulsified silicone oil particles or other impurities, which need to be removed by filtering. You can use a 100-mesh filter to filter. After filtration, if you need to adjust the performance of the defoamer, such as adjusting the viscosity of the emulsion, you can add an appropriate amount of thickener or diluent. The amount of thickener added is generally adjusted according to the required viscosity. For example, adding 1% CMC can appropriately increase the viscosity of the emulsion; if dilution is required, add an appropriate amount of deionized water to make the defoamer reach the required concentration and performance.

[0029] For some application scenarios with high requirements for stability, the prepared defoamer can be tested for stability. The defoamer can be observed under different temperatures (such as 4°C, 25°C, 40°C) and storage times (such as 1 day, 7 days, 30 days) to check whether the emulsion is stratified or demulsified. If stability problems occur, they can be solved by adjusting the type and amount of emulsifier, adding stabilizer, etc.

[0030] The preparation process of the curing agent includes the following steps: Step 1: Select diethylenetriamine as the main component of the curing agent, and select other additives as auxiliary agents to adjust the performance of the curing agent. The purity of amine compounds is required to be high, generally above 99% to ensure the quality of the curing agent, because impurities may affect the speed and degree of the curing reaction. For example, if ethylenediamine contains impurities such as moisture, bubbles may be generated during the curing process, affecting the performance of the cured product; For example, in order to extend the application period of the curing agent, a small amount of retarder, such as salicylic acid, can be added. The amount of retarder is generally adjusted according to the specific curing requirements, usually 0.1%-5% of the mass of the amine raw material; Step 2: placing diethylenetriamine and propylene oxide in a reaction kettle equipped with a stirrer, a thermometer and a reflux condenser for chemical reaction; Usually it involves reactions with other compounds, such as the reaction of fatty amines with compounds such as propylene oxide, which is carried out in a reactor equipped with a stirrer, a thermometer and a reflux condenser. First, the fatty amine is added to the reactor and heated to 100°C, and then propylene oxide is slowly added dropwise. During the reaction, the dropping speed and reaction temperature must be strictly controlled. The dropping speed is 2mL / min to prevent the reaction from being too violent. The reaction time is 6h. This reaction can modify the fatty amine and change its activity and curing properties. Step 3: Filter the solid after the chemical reaction to remove the unreacted raw materials or reaction by-products; If further refining is required, vacuum distillation and other methods can be used to remove low-boiling impurities and unreacted small molecules. The temperature and pressure of vacuum distillation should be adjusted according to the boiling point and other properties of the curing agent. For example, for some low molecular weight fatty amine curing agents, the vacuum distillation temperature can be controlled at 100°C and the pressure is 10kPa.

[0031] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A special anti-corrosion and wear-resistant coating for heat exchanger, characterized by: The formula includes the following parts by mass: 10-20 parts of epoxy resin, 25-35 parts of polyurethane resin, 10-25 parts of zinc powder, 18-38 parts of zinc phosphate, 8-18 parts of silicon carbide, 15-37 parts of aluminum oxide and 10-22 parts of additives; The auxiliary agent includes a dispersant, a defoamer and a curing agent in parts by mass.

2. A method for preparing a special anti-corrosion and wear-resistant coating for a heat exchanger, characterized in that: The method comprises the following preparation steps: Step 1: Pre-treat the raw materials, sieve the anti-corrosion pigments such as zinc powder and zinc phosphate and the wear-resistant fillers such as silicon carbide and aluminum oxide respectively to remove large particle impurities, and heat the film-forming materials such as epoxy resin and polyurethane resin to an appropriate temperature to reduce their viscosity for subsequent mixing operations; Step 2: Mix and disperse the pretreated raw materials, put the pretreated film-forming material into a high-speed disperser, add a dispersant under low-speed stirring, then slowly add anticorrosive pigments and wear-resistant fillers, and increase the stirring speed to fully disperse the anticorrosive pigments and wear-resistant fillers in the film-forming material, and then add a defoaming agent to eliminate bubbles generated during the stirring process; Step 3: Grind and refine the anticorrosive pigment and wear-resistant filler in the film-forming material. Put the mixed and dispersed coating into a sand mill for grinding. The particles of the anticorrosive pigment and wear-resistant filler can be further refined by grinding. Step 4: Adjust the viscosity. Add an appropriate amount of curing agent to the ground paint and stir slowly and evenly. Finally, use a thinner to adjust the viscosity of the paint according to the construction requirements of the paint.

3. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchanger according to claim 2, characterized in that: In the step 1, screening is performed using a 200-300 mesh screen. In order to prevent the anti-corrosion pigment and the wear-resistant filler from being oxidized and thus affecting their performance, the anti-corrosion pigment and the wear-resistant filler need to be processed in an inert gas environment.

4. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchangers according to claim 2, characterized in that: In the step 1, the epoxy resin needs to be heated to 40-60° C., and the polyurethane resin needs to be heated to 50-70° C. At the same time, attention should be paid to stirring during the heating process to prevent local overheating.

5. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchanger according to claim 2, characterized in that: In the step 2, the low-speed stirring rate is 300-500 r / min, and the stirring time is 5-10 min, the high-speed stirring rate is 1000-1500 r / min, and the stirring time is 30-60 min, and after adding the defoaming agent, high-speed stirring is required for 10-15 min.

6. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchangers according to claim 2, characterized in that: The grinding medium in step three is glass beads or zirconium oxide, and the particle size of the medium is 0.8-1.2 mm, and the grinding time is 2-4 hours. The fineness of the coating after grinding is 30-50 μm, thereby improving the density and glossiness of the coating.

7. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchanger according to claim 2, characterized in that: The amount of curing agent added in step 4 is calculated based on the epoxy equivalent of the film-forming substance. For example, the amount of amine curing agent is usually 0.8-1.2 times the epoxy equivalent of epoxy resin. The viscosity of the coating needs to be controlled at 60-80s during construction, and the coating after adjusting the viscosity can be used for anti-corrosion and wear-resistant coating of the heat exchanger after filtering through a 100-150 mesh filter.

8. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchangers according to claim 2, characterized in that: The preparation process of the dispersant comprises the following steps: S1: After selecting the monomer, the initiator is prepared, and then the solvent is prepared; S2: First, a reaction device is built, then the monomer is prepolymerized, and finally the monomer is continuously added to make the polymer chain grow continuously to form an anionic polymer with a certain molecular weight; S3: firstly prepare an alkali solution, then add the alkali solution to the anionic polymer for neutralization, convert the acidic functional groups (such as carboxyl groups) in the polymer into salt form, so that the dispersant has better water solubility and dispersibility; S4: The neutralized dispersant solution contains a small amount of unreacted monomers, polymer gel and other impurities, which need to be removed by filtering. The filtered solution is then dried and concentrated to obtain a solid dispersant.

9. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchanger according to claim 2, characterized in that: The preparation process of the defoamer comprises the following steps: S①: Select dimethyl silicone oil as the main component of the defoamer, and select dimethyl silicone oil with a viscosity between 100-1000mPa・s according to the specific application scenario. At the same time, prepare an emulsifier for dispersing silicone oil in the water phase, as well as other additives that can improve the performance of the defoamer; S②: Put the silicone oil and emulsifier solution into a reactor equipped with a stirrer and a thermometer, first stir at a low speed of 300-500r / min to make the silicone oil and emulsifier preliminarily mixed, then increase the stirring speed to 1000-2000r / min, and use a homogenizer or ultrasonic emulsifier to assist emulsification; S③: Filter the emulsified defoamer to remove incompletely emulsified silicone oil particles or other impurities, and then adjust the viscosity of the defoamer emulsion according to the amount of thickener added.

10. The method for preparing a special anti-corrosion and wear-resistant coating for heat exchangers according to claim 2, characterized in that: The preparation process of the curing agent comprises the following steps: Step 1: Select diethylenetriamine as the main component of the curing agent, and select other additives as auxiliary agents in order to adjust the performance of the curing agent; Step 2: placing diethylenetriamine and propylene oxide in a reaction kettle equipped with a stirrer, a thermometer and a reflux condenser for chemical reaction; Step 3: Filter the solid after the chemical reaction to remove incompletely reacted raw materials or reaction by-products.

Citation Information

Patent Citations

  • Marine anticorrosive coatings

    CN104277664A

  • Metal water-soluble anticorrosive coating

    CN106519920A

  • Epoxy resin anticorrosive coating and preparation method thereof

    CN108359347A

  • Anticorrosive coating composition

    CN111748261A

  • Corrosion-resistant anticorrosive coating for fasteners

    CN112391099A

Cited By

  • Protection method for low-temperature corrosion of high-sodium coal pyrolysis gas

    CN120865971A

  • Coating based on magnetic regulation and control as well as preparation method and application thereof

    CN122168147A